PENGARUH ETOS KERJA DAN PEMBERIAN INSENTIF TERHADAP PENINGKATAN PRESTASI KERJA KARYAWAN PADA DIVISI PRODUKSI PT YONGJIN JAVA SUKA GARMENT - Eka Sutisna; Fais Kaldun; Intan Puspita Rini; M. Gelar Faisal (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The purpose of this research was to determine the effect of work ethic and incentives on improving employee performance. This study uses quantitative methods. The sample in this study were line 1 employees at the production division of PT Yongjin Javasuka Garment, totaling 40 people. Data collection technique in this study is a questionnaire. Data analysis technique in this study using multiple linear regression data analysis. Based on the result of the study obtained the reslut of multiple linear regression test Ŷ = 15,079 + 0,212X1 + 0,461X2. Simultaneously work ethics and provision of incentives have a positive and significant effect on improving employee performance in the production division of PT Yongjin Javasuka Garment with a significant value of 0,000 less than 0,05. And a calculated Fcount value of 15,037 > Ftable = 3.25 . The results of this study are that work ethic has not significant effect on improving employee performnace with a significant value of 0,062 where the value is > 0,05 or with an observation scale the tcount value is 1,927 > ttable 1,687. Giving incentives has a positive and significant effect on improving employee performance with a significant value of 0,004 where the value is < 0,05 or with an observation scale tcount 3,086 > ttable 1,687.